Mask making - Bodonyi, Kriszta. (HUSH School of Mime and Non-Verbal Theatre, 1994)
The vide films about Mime, Mask and Mask Making are practical manuals for educators and students demonstrating the fundamental techniques of mime, performing with mask, mask making and their applications in the classroom. They describe the basic rules and procedures, provide physical exercies and a variety of ideas and suggestions to develop skills and stimulate interset in the three subjects.